Development of a one-step multiplex RT-qPCR method for rapid detection of bovine diarrhea viruses - Yang, Dequan; Ma, Li; Yang, Zhongping; Yang, Xianchao; Wang, Jian; Ju, Houbin; Lu, Chunguang; Weng, Yonggang; Zhao, Heping; Shen, Haixiao; Li, Xin; Ge, Feifei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionViral calf diarrhea poses a significant challenge to the cattle industry worldwide due to its high morbidity and mortality rates, leading to substantial economic losses. The clinical symptoms associated with various diarrhea pathogens often overlap, complicating accurate diagnosis; thus, there is an urgent need for rapid and precise diagnostic methods to improve prevention and treatment efforts. In this study, we developed a one-step multiplex reverse-transcription quantitative real-time polymerase chain reaction (mRT-qPCR) that enables the simultaneous detection of three key viral pathogens responsible for calf diarrhea: bovine kobuvirus (BKoV), bovine astrovirus (BoAstV), and bovine torovirus (BToV). However, development of accurate and rapid methods to distinguish these three viruses is helpful for the early detection, disease surveillance, and control of viral calf diarrhea.MethodsSpecific primers and minor groove binder (MGB)-based probes were designed targeting the 3D region of BKoV, ORF1 region of BoAstV, and N region of BToV. The sensitivity, specificity, and reproducibility ability were evaluated for the mRT-qPCR. Further, 80 bovine fecal samples were subjected to the mRT-qPCR, and the results were verified using conventional reverse-transcription PCR (RT-PCR) or PCR methods and sequencing methods.ResultsThis novel method demonstrated high sensitivity and specificity,achieving a detection limit of 24 copies/mL for each pathogen. Furthermore, the assay exhibited excellent reproducibility, with coefficients of variation below 1.5%, a strong linear correlation (R2 > 0.996), and an amplification efficiency between 90% and 110%. Validation with 80 clinical samples from both diarrheic and non-diarrheic cattle across four farms in Shanghai showed a high degree of concordance with RT-PCR, with positive detection rates for BKoV, BoAstV, and BToV at 28.75%, 8.75%, and 3.75%, respectively, highlighting the predominance of BKoV and BoAstV. Notably, this study represents the first identification of BKoV, BoAstV, and BToV in the Shanghai region.DiscussionThe mRT-qPCR is a robust, rapid, and simple tool for identifying viral pathogens associated with calf diarrhea, facilitating the development of effective prevention and control measures that are vital for the future sustainability of the cattle industry.